Does swallow rehabilitation improve recovery of swallow function after treatment for advanced head and neck cancer - Tsou, Yung-An; Meng, Nai-Hsin; Chang, Wen-Dien; Hua, Chun-Hung (Scientific reports, 2025)
This study aimed to assess the prevalence, severity, and progression of swallowing impairments in head and neck cancer (HNC) patients before and after treatment, using videofluoroscopy with the Modified Barium Swallow Impairment Profile (MBSImP) protocol. We retrospect survey 90 HNC patients was divided into rehabilitation (receiving swallowing rehabilitation) and non-rehabilitation groups. All participants underwent a videofluoroscopic swallowing study with MBSImP, the Penetration-Aspiration Scale (PAS), and the Swallowing Performance Status (SPS) scale, along with assessments using the EAT-10 and Functional Oral Intake Scale (FOIS) at baseline, and at 1 and 3 months post-treatment. In all patients, MBSImP, PAS, and FOIS scores worsened one month after therapy. However, patients who performed swallow exercises demonstrated statistically significant improvements in swallowing function (FOIS and EAT-10) and related quality of life (EAT-10, Reflux Symptom Index) after three months of rehabilitation. High aspiration rates (poor PAS scores) were observed in all HNC patients post-treatment, peaking at 1 month and persisting over time. Notably, the rehabilitation group showed recovery of swallowing function to pre-treatment levels. Dysphagia is a significant and enduring side effect that impacts the quality of life in HNC patients undergoing multimodal treatment. The study suggests that a proactive swallowing rehabilitation program can positively influence outcomes, particularly after 3 months of rehabilitation.